2016
DOI: 10.1080/00131881.2016.1165410
|View full text |Cite
|
Sign up to set email alerts
|

On the supranational spell of PISA in policy

Abstract: Background PISA results appear to have a large impact upon government policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 44 publications
0
63
0
2
Order By: Relevance
“…Such efforts might not take into account the cultural context of national educational systems. Analyses by Baird et al (2016) and Nortvedt (2018) have indicated that the national context influences policy decisions to a large extent.…”
Section: Policy Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such efforts might not take into account the cultural context of national educational systems. Analyses by Baird et al (2016) and Nortvedt (2018) have indicated that the national context influences policy decisions to a large extent.…”
Section: Policy Issuesmentioning
confidence: 99%
“…To summarise, a two-directional, reciprocal relationship may be seen between policy and mathematics education, where assessment outcomes inform and influence policymaking (Baird et al 2016) and educational policies influence assessment, teaching, or education programmes (Cai et al , 2016Middleton et al 2015). For instance, the phenomenon of 'teaching to the test' (Hamilton et al 2007) is usually interpreted as a negative policy influence on mathematics education.…”
Section: Policy Issuesmentioning
confidence: 99%
“…Based on the media attention ILSAs receive, particularly after the release of PISA results and international rankings (Baird et al, 2016;Meyer & Benavot, 2013), it appears as though the increased participation in ILSA-related projects and studies has had a profound effect on education and policy discourses globally (Breakspear, 2012;Hopfenbeck et al, 2017), but not necessarily in the ways that make direct causal policy linkages easy to identify. 12 Our review of the literature indicates that some governments appear to have implemented policy changes as a result of ILSAs scores, while others seem to have used these scores to justify and/or accelerate pre-existing school reforms.…”
Section: Review Of the Literature: Ilsas/glms As Tools Of Legitimationmentioning
confidence: 99%
“…4 Forty-three countries participated in PISA 2000, for instance, compared with 76 countries in PISA 2015 (OECD, n.d.). 5 It should be noted that IEA studies have been primarily used for research purposes by national experts, whereas the OECD has an aggressive role as a policy advisor and interpreter of its own findings. 6 As part of ASER's administration of the Annual Status of Education Report (ASER) survey in India.…”
Section: Some Of the Most Well-known And Influential Ilsas Include Thmentioning
confidence: 99%
“…Ireland had its own 'PISA shock' (Baird et al 2011) following the publication of the 2009 results and a suite of policy measures was introduced to respond to perceived deficiencies highlighted by the results, most notably through the national literacy and numeracy strategy in 2011 (Department of Education and Skills [DES] 2011).…”
Section: Introductionmentioning
confidence: 99%